Stepping stones - Knisley, Lucy (RH Graphic, 2020)
A young girl named Jen feels like she never gets what she wants--she never wanted to leave her city, move in with her mom and her mom's boyfriend on their farm, and leave all her friends and real dad behind. She especially did not want to get two new "sisters," but all the bittersweet adventures with them on the farm may just be what she needs.